Clinical applications of capillary electrophoresis methods and protocols - Phillips, Terry ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This second edition volume provides a valuable source of information on the application of capillary electrophoresis (CE) and the many different aspects of clinical medicine. Chapters divided into seven parts focus on applications in clinical chemistry and small molecule analysis, applications in drug analysis, examples of CE applied to metabolomics, application in pediatrics, CE analysis on oncology, and CE analysis in virology. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Clinical Applications of Capillary Electrophoresis: Methods and Protocols, Second Edition aims to become a resource not only for clinical chemists, but also physicians and scientists who wish to apply these techniques to diagnosis and clinical research